A universalidade da mulher que se tornou Nossa Senhora e sua relação primitiva-contemporânea na história, arte, religião e semiótica - Toda, Egidio Shizuo (2019)
The present work has the purpose of bringing together historical and artistic facts, as well as elements of the tradition of the early Christian religion, of understanding the figure of Mary. She is the Mother of Jesus, a woman who, in addition to the strength and vigor with which she faced challenges of his life, she continued to exert decisive influence throughout the history of Christianity, both in the East and in the West. Many people have revealed healing miracles in the name of Mary, scientifically proven. In discussing the phenomenon of the miracle, we limit ourselves by method, to address the affluence of believers to five great sanctuaries: Fatima, Lourdes, Aparecida, Kibeho, and Medjugorje, because these are where the most significant influxes of pilgrims have been registered annually. Apparitions, miracles, and devotions make Mary the most powerful woman on earth, and she still exerts an influence on women's empowerment. The study, in addition to covering the religious aspect and its childhood, adolescence, and adulthood, also provides a historical retrospective of how devotion to it evolved, with particular emphasis on the Eastern Roman Empire. Not without reason, our great focus is also on the analysis of sacred art, at the confluence of the Marian works of two great exponents: Theodore Metochites, with its Byzantine mosaics of the 14th century Church of St. Savior of Chora, today Istanbul, Turkey and Claudio Pastro , with its modern tiles from the 21st century Basilica of Our Lady of Aparecida, in Aparecida, Brazil. This paper also covers the following approaches. The analogy, the investigation of sacred art and the need to preserve the cultural heritage of the east and the west. The relationship between the artist, his work, and the creative process in the examination of semiotics in contemporary times, exposed in Chora and Aparecida, through the images of Christ Pantocrator and the Immaculate Virgin. The transition of art, education, and cultural history navigating between the aesthetic and the liturgical in its interdisciplinary process, aiming to recognize the universal and timeless state of Christian art.